Vpliv grškega templja v arhitekturi - Marinko, Jože (AR. Arhitektura, raziskave, 2004)
The Greek temple is an architectural creation that has had indispensable influence on Western architecture since its beginnings. According to its content, the temple had key significance in Greek cities, thus it directly affected all other types of public buildings. The Romans used the temple's layout in its original form or merged it with Etruscan arcades into a new image, which marked all 1ater classical architecture. With orders, which were codified by Renaissance theoreticians and used by Renaissance architects, the theme of Greek temples became the starting point for all architectural enterprises in various style periods, all the way to modernism. Even contemporary architecture has accepted many composition principles, which were most clearly established on the Greek temple.The article wishes to rekindle our consciousness about architectural qualities of the Greek temple and point out its guiding role in later architectural periods. It simultaneously proves the statement that the original theme (the temple) can be originally interpreted (redesigned) according to architectural orientations of a certain time. Thus it indirectly responds to one of the key issues in contemporary art and also architecture, namely, the decisive criteria, when evaluating the quality of a creation, cannot be its disengagement from the original. A creative person when working always looks to a reference, whatever its name: ideal, motif or startingpoint.
Keywords: architecture; arhitektura; antična arhitektura; grški tempelj; sodobna arhitektura; vplivi